Fiscal Sustainability and Country Risk Profile: Empirical Evidence in Indonesia - Mufid, Hafizh Azka; Widyawati, Diah (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research examines fiscal sustainability by considering the fiscal behavior of different government regimes and analyzing the correlation between fiscal sustainability and a country's risk profile using the VARX method, with the real effective exchange rate (REER) as an exogenous variable.Research Objectives: This study aims first to determine whether Indonesia's fiscal conditions are sustainable across different government regimes. It then investigates whether a significant link exists between Indonesia's fiscal sustainability and its country's risk profile, as reflected by sovereign spreads from 2005 to 2024.Research Methods: This study used the Vector Autoregressive Exogenous (VARX) method to capture endogeneity, exogeneity, simultaneity, direct effects, indirect effects, and shock-response of the variables used to measure the relationship between fiscal sustainability and sovereign risk.Empirical Results: The findings indicate a significant relationship between fiscal sustainability and country risk, where an increase in the primary balance raises investor risk perception. Meanwhile, if debt management policies are implemented prudently and effectively, a rise in the debt-to-GDP ratio does not always widen the sovereign spread.Implications: These results suggest that, despite differences in government regimes, policymakers should focus on strengthening the government's ability to manage debt prudently and either generate a primary balance surplus or reduce the deficit by sustainably enhancing revenue and spending policies to maintain fiscal sustainability and lower the country's risk profile.JEL Classification: H62, H60, H63, C32How to Cite:Mufid, A.H., & Widyawati, D. (2025). Fiscal Sustainability and Country Risk Profile: Empirical Evidence in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 163-178. https://doi.org/10.15408/sjie.v14i1.45801.